2010
DOI: 10.1002/ccd.22363
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal balloon aortic valvuloplasty—predictive value of current risk score algorithms for treatment strategies

Abstract: No prospectively tested criteria for patient selection (biventricular vs. univentricular) are available for critically ill newborns with AoS. Retrospective application of the current risk scores showed unsatisfactory results. Treatment decisions are based on local experience and expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
6
0
2
Order By: Relevance
“…The causes of death were multifactorial: In four cases, death was considered secondary to BAV complications, and in eight cases (8/11-72 %), patients were finally diagnosed with a ''borderline LV'' with abnormal left heart structures or non-compliant LV, clearly associated with an increased risk of poor results and death [14]. When neonates are diagnosed with a ''borderline LV,'' predicting which is suitable for biventricular repair remains a substantial challenge [2,5,11] and the presence of endocardial fibroelastosis with LV diastolic dysfunction appears to be a more significant risk factor than LV volume or dimensions [14]. LV systolic dysfunction preceding BAV also tended to be associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of death were multifactorial: In four cases, death was considered secondary to BAV complications, and in eight cases (8/11-72 %), patients were finally diagnosed with a ''borderline LV'' with abnormal left heart structures or non-compliant LV, clearly associated with an increased risk of poor results and death [14]. When neonates are diagnosed with a ''borderline LV,'' predicting which is suitable for biventricular repair remains a substantial challenge [2,5,11] and the presence of endocardial fibroelastosis with LV diastolic dysfunction appears to be a more significant risk factor than LV volume or dimensions [14]. LV systolic dysfunction preceding BAV also tended to be associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Aortic regurgitation may occur after aortic balloon valvuloplasty (AoVP) in patients with borderline left ventricle. 5 Aortic regurgitation after AoVP is a known risk factor for a subsequent Norwood operation. 6 In fact, in this old publication, severe aortic regurgitation was a contra indication for a Norwood operation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, in line with the findings achieved by other authors, confirmed good effec tiveness of BAV in reducing PG across the aor tic valve directly after the procedure in all age groups. 4,5,[10][11][12][13][14][15][16] The severity of AR assessed direct ly after the procedure was mostly moderate in 98.5% of patients and severe only in 1 patient. The published studies reported severe AR di rectly after the procedure at rates ranging from 0% to 40%, depending on the grading scale (a 3 or 4point scale), assessment method (angio graphic or echocardiographic), definition of se vere AR (grade ≥2 or grade ≥3), and timing of the procedures.…”
Section: What's New?mentioning
confidence: 98%